Novel Lanthanide(III) Porphyrin-Based Metal-Organic Frameworks: Structure, Gas Adsorption, and Magnetic Properties - Király, Nikolas; Zeleňák, Vladimír; Lenártová, Nina; Zeleňáková, Adriana; Čižmár, Erik; Almáši, Miroslav; Meynen, Vera; Hovan, Andrej; Gyepes, Róbert (ACS omega, 2021)
The present work focuses on the hydrothermal synthesis and properties of porous coordination polymers of metal-porphyrin framework (MPF) type, namely, {[Pr4(H2TPPS)3]·11H2O} n (UPJS-10), {[Eu/Sm(H2TPPS)]·H3O+·16H2O} n (UPJS-11), and {[Ce4(H2TPPS)3]·11H2O} n (UPJS-12) (H2TPPS = 4,4',4″,4‴-(porphyrin-5,10,15,20-tetrayl)tetrakisbenzenesulfonate(4-)). The compounds were characterized using several analytical techniques: infrared spectroscopy, thermogravimetric measurements, elemental analysis, gas adsorption measurements, and single-crystal structure analysis (SXRD). The results of SXRD revealed a three-dimensional open porous framework containing crossing cavities propagating along all crystallographic axes. Coordination of H2TPPS4- ligands with Ln(III) ions leads to the formation of 1D polymeric chains propagating along the c crystallographic axis. Argon sorption measurements at -186 °C show that the activated MPFs have apparent BET surface areas of 260 m2 g-1 (UPJS-10) and 230 m2 g-1 (UPJS-12). Carbon dioxide adsorption isotherms at 0 °C show adsorption capacities up to 1 bar of 9.8 wt % for UPJS-10 and 8.6 wt % for UPJS-12. At a temperature of 20 °C, the respective CO2 adsorption capacities decreased to 6.95 and 5.99 wt %, respectively. The magnetic properties of UPJS-10 are characterized by the presence of a close-lying nonmagnetic ground singlet and excited doublet states in the electronic spectrum of Pr(III) ions. A much larger energy difference was suggested between the two lowest Kramers doublets of Ce(III) ions in UPJS-12. Finally, the analysis of X-band EPR spectra revealed the presence of radical spins, which were tentatively assigned to be originating from the porphyrin ligands.